WILLINGNESS TO PAY (WTP) TO MEASURE THE EXISTING AND THE HERITAGE VALUES OF AGRICULTURE WETLAND (Case Study of Banjar Regency, South Kalimantan) - Maleimakuni, Alexander Victor; Fatah, Luthfi; Yunani, Ahmad; Adriani, Ade (Technium Sustainability, 2024)
Agricultural wetlands are rice fields in the tidal swamps area in South Kalimantan. They result from the Banjar Community converting marginal land into productive land over the generations. Now, its existence is threatened due to land conversion. This research aims to find the land existence and heritage value (LEHV) of the agricultural wetlands covering an area of 60,862 hectares in Banjar Regency on the assessment in 2020. The economic valuation method used is the contingent valuation method (CVM), which measures willingness to pay (WTP) landowners of non-agricultural property around agricultural wetlands who enjoy environmental services from agricultural wetlands. WTP is measured by a willingness to pay a significant additional annual land and building tax from the non-agricultural property they own and an incentive to farmers and landowners to continue to maintain the existence of agricultural wetlands so that they can be passed on to future generations. WTP data collection uses a preference survey by distributing questionnaires and interviews. The number of research respondents was seventy-five, spread across the Banjar Regency. The average WTP to maintain the agricultural wetlands in Banjar Regency is IDR 39,500, and the total WTP or LEHV an area of 60,862 hectares on assessment date 31 December 2020, economic valuation results using the CVM amounting to IDR 22,342,582,500.00 or IDR 367,102 per hectare.